Penerapan Pendidikan Matematika Realistik (PMR) untuk Meningkatkan Kemampuan Literasi Matematika Siswa Kelas IV SDN 03 Cimaung Serang - Usep Sholahudin (Universitas Serang Raya, 2018)
This study is a Classroom Action Research (CAR) with the subject of this study is the fourth grade students SDN 03 CIMAUNG SERANG which amounted to 30 students, 16 students and 14 female students. The research procedure uses stages: planning, execution, observation, and reflection. Data collection techniques used were interviews, observations, tests, documentation, and field notes. The instruments used are interview guides, observation sheets, worksheets, tests, documentation, and field notes. Data analysis technique in this research is descriptive qualitative and quantitative data analysis. The results of this study indicate that the ability of students' mathematics literacy grade IV SDN 03 CIMAUNG SERANG has increased from pre-action to cycle I then to cycle II after applied Realistic Mathematics Education (RME) in the process of learning mathematics.